2020
DOI: 10.3389/fphar.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Nordihydroguaiaretic Acid: From Herbal Medicine to Clinical Development for Cancer and Chronic Diseases

Abstract: Nordihydroguaiaretic acid (NDGA) is a phenolic lignan obtained from Larrea tridentata, the creosote bush found in Mexico and USA deserts, that has been used in traditional medicine for the treatment of numerous diseases such as cancer, renal, cardiovascular, immunological, and neurological disorders, and even aging. NDGA presents two catechol rings that confer a very potent antioxidant activity by scavenging oxygen free radicals and this may explain part of its therapeutic action. Additional effects include in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 181 publications
(231 reference statements)
0
37
0
Order By: Relevance
“…Other prominent overlapping interactors include the IFITs (Interferoninduced protein with tetratricopeptide repeats), IFIT1 and IFIT2, antiviral proteins that function as sensors of viral single-stranded RNAs to inhibit expression of viral messenger RNAs (Diamond & Farzan, 2013). Nsp3 DTM also interacts with the antiviral proteins SAMHD1, which binds to nucleotides and depletes cellular dNTPs, and 1'-5'-oligoadenylate synthase 3 (OAS3), another interferon-induced gene that inhibits viral replication by degrading viral RNA (Li et al, 2016). In addition, both PLpro and Nsp3 DTM interact with the multifunctional ATP-dependent RNA helicase DDX3X, which promotes IRF3 activation leading to the production of the type I interferons, IFNa and IFN-b (Soulat et al, 2008).…”
Section: Interactome Of Plpro and Nsp3mentioning
confidence: 99%
See 1 more Smart Citation
“…Other prominent overlapping interactors include the IFITs (Interferoninduced protein with tetratricopeptide repeats), IFIT1 and IFIT2, antiviral proteins that function as sensors of viral single-stranded RNAs to inhibit expression of viral messenger RNAs (Diamond & Farzan, 2013). Nsp3 DTM also interacts with the antiviral proteins SAMHD1, which binds to nucleotides and depletes cellular dNTPs, and 1'-5'-oligoadenylate synthase 3 (OAS3), another interferon-induced gene that inhibits viral replication by degrading viral RNA (Li et al, 2016). In addition, both PLpro and Nsp3 DTM interact with the multifunctional ATP-dependent RNA helicase DDX3X, which promotes IRF3 activation leading to the production of the type I interferons, IFNa and IFN-b (Soulat et al, 2008).…”
Section: Interactome Of Plpro and Nsp3mentioning
confidence: 99%
“…Disulfiram is a thiocarbamate drug (commercially available as Antabuse®) that has received FDA approval for the treatment of alcoholism and has been in use for more than 60 years (Johansson, 1992). Disulfiram has been previously identified by in silico screening and fluorescence resonance energy transfer assay to inhibit the main SARS-CoV-2 Cys-protease, Mpro (Lobo-Galo et al, 2020;Jin et al, 2020). Disulfiram also inhibits PLpro CoV2 and Nsp3 with similar potencies, 0.69 and 0.66 µM in the MALDI-TOF-based assay, and between 1 and 2.5 µM when assessed by gel-based orthogonal assay ( Figure 3D-E).…”
Section: S3a-c)mentioning
confidence: 99%
“…NDGA belongs to the class of lignans with catecholic structures ( Figure 1 ). It has a wide range of biological activities [ 23 ]. To date, no studies have reported the biological effects of NDGA on COMT.…”
Section: Discussionmentioning
confidence: 99%
“…NDGA/Masoprocol is exerting pleiotropic actions in many systems, particularly cancer cells. It is a phenolic ligand from the plant genus Larrea, used in traditional medicine in Mexico and SouthWest USA to treat many diseases as different as rheumatism, diabetes, pain, inflammation (31). NDGA has anti-oxidant and electrophilic properties and therefore has been reported to interfere with many cellular enzymes such as Lipoxygenases (LOX) but also with several tyrosine kinases (Insulin Receptor, HER2) or phosphatases such as PTEN or DUSPs.…”
Section: Discussionmentioning
confidence: 99%